Association between MTHFR microRNA binding site polymorphisms and methotrexate concentrations in Chinese pediatric patients with acute lymphoblastic leukemia. (3rd November 2017) - Wang, Shu‐Mei; Zeng, Wei‐Xin; Wu, Wan‐Shui; Sun, Lu‐Lu; Yan, Dan
Abstract: Background: The pharmacokinetics and therapeutic response to methotrexate (MTX) display large variability in the treatment of acute lymphoblastic leukemia (ALL). The aim of the present study was to investigate the association of two microRNA (miRNA) binding site polymorphisms (rs3737966 G > A and rs35134728 DEL/TTC) in the 3′‐untranslated region of MTHFR with serum MTX concentrations, in a Chinese pediatric population with ALL. Methods: Genotyping for MTHFR rs3737966 and rs35134728 in 144 children with ALL was performed using the Sequenom MassArray system (Sequenom, San Diego, CA, USA). Serum MTX concentrations were measured by a fluorescence polarization immunoassay 24 h ( C 24h ) and 42 h ( C 42h ) after administration. The effects of the polymorphisms on concentration‐to‐dose ( C / D ) ratios of MTX were assessed. Results: Complete linkage disequilibrium between rs3737966 and rs35134728 polymorphisms ( r 2  = 1) was found in the study population. The minor allele frequency observed in the present study (17.4%) was significantly lower than those in European and African samples reported in the 1000 Genomes Project (42.9% and 63.9%, respectively; p  < 0.01). The C / D ratios of MTX at 24 and 42 h for the TTC/TTC‐A/A haplotype carriers (11.74 and 0.07 μmol/l per g/m 2, respectively) were significantly lower than those in DEL/DEL‐G/G or DEL/TTC‐G/G haplotype carriers (12.49 and 0.09 μmol/l per g/m 2, respectively; p  < 0.05). Computational predictions suggested that the two polymorphisms overlapped with putative binding sites of several miRNAs. Conclusions: The rs3737966 and rs35134728 polymorphisms in MTHFR were associated with serum MTX concentrations. The findings of the present study indicate that miRNAs might be involved in the post‐transcriptional regulation of MTHFR.